Pengaruh Keterlibatan, Kemampuan Teknis, dan Pelatihan Kerja Pemakai pada Kinerja Sistem Informasi Akuntansi - Krisna Dewi, Ni Putu; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 30 No 4 (2020)DO - 10.24843/EJA.2020.v30.i04.p15, 2020)
The purpose of this study was to determine the Effect of Engagement, Technical Capability, and User Job Training on Accounting Information System Performance. This research was conducted at the Department of Industry and Trade Denpasar City. The number of respondents was 50 respondents, with non-probability sampling method. The analysis technique used is multiple linear regression analysis techniques. The analysis shows that the involvement, technical ability, and work training of users has a positive effect on the performance of accounting information systems. This shows that the higher the involvement of users, technical capabilities, and job training owned by Denpasar City Industry and Trade staff the performance of the accounting information system produced will increase. Keywords: User Involvement; User Technical Capability; User Job Training; Accounting Information System Performance.